Mashup Indices of Development - Ravallion, Martin (2012)
Countries are increasingly being ranked by some new "mashup index of development," defined as a composite index for which existing theory and practice provides little or no guidance to its design. Thus the index has an unusually large number of moving parts, which the producer is essentially free to set. The parsimony of these indices is often appealing -- collapsing multiple dimensions into just one, yielding unambiguous country rankings, and possibly reducing concerns about measurement errors in the component series. But the meaning, interpretation and robustness of these indices are often unclear. If they are to be properly understood and used, more attention needs to be given to their conceptual foundations, the tradeoffs they embody, the contextual factors relevant to country performance, and the sensitivity of the implied rankings to changing the data and weights. In short, clearer warning signs are needed for users. But even then, nagging doubts remain about the value-added of mashup indices, and their policy relevance, relative to the "dashboard" alternative of monitoring the components separately. Future progress in devising useful new composite indices of development will require that theory catches up with measurement practice.